Identificación y prospección de nematodos en el sistema agroecológico en el campus Salache, cantón Latacunga, provincia de Cotopaxi, 2022-2023. - Villarroel Camalli, Karen Dayana (2023)
The present investigation, identification and prospection of nematodes in the Salache Campus was quantified by the number of nematodes individuals in the lot of the agroecological vegetable production system, 12 soil samples were collected at a depth of 5cm, 10cm and 15 cm, using the Zig Zag method, 100g of soil were weighed with a soil auger and then placed in sealed and labeled Ziploc bags to be transported to the laboratory where they were homogenized, sieved, centrifuged and observed under the microscope, where at a 5cm depth, Scutellonema sp. with 40 individuals, Helycotilenchus sp. with 32 individuals and Meloydogyne sp. with 11 individuals. At a 10cm depth Scutellonema sp. with 25 Helycotilenchus sp. with 8 individuals and Meloydogyne sp. with 6 individuals. At a 15 cm depth Scutellonema sp. with 19 Helycotilenchus sp. with 6 individuals and Meloydogyne sp. with 3 individuals. A total of 150 nematodes were found in the lot. According to the results obtained and compared in the agroecological system, since it is a purely organic production, the soil is healthy and fertile and therefore the capital gain with high organic matter and biodiversity increases. Comparing the diversity of nematodes found in the research with the crops in the agroecological system, since there is no infection by them, all the plants diversity that exist have grown normally and without any problem and because of the size and vigorousness the cost of the plants increases.